Effects of molecular targeting agents and immune-checkpoint inhibitors in patients with advanced cancer who are near the end of life. Issue 6 (December 2021) - Hiramoto, Shuji; Taniyama, Tomohiko; Kikuchi, Ayako; Hori, Tetsuo; Yoshioka, Akira; Inoue, Akira
Abstract: Background: In recent years, the use of both molecular targeting agents (MTAs) and immune-checkpoint inhibitors (ICIs) tend to occupy important positions in systemic anticancer therapy (SACT). The objective of this study is to describe the predictors of SACT include both MTAs and ICIs near the end of life (EOL) and the effect on EOL care in patients with advanced cancer. Methods: We analyzed all patients who died of advanced cancer from August 2016 to August 2019, and we analyzed the survival time of patients who underwent anticancer agents excluded due to the loss of information about the last administration of SACT. The primary endpoint of this study was to identify predictors during the last administration of SACT near EOL. Results: In a multivariate analysis, the Eastern Cooperative Oncology Group performance status (ECOG-PS) (ORs 33.781) was significantly related factors within 14 days of death from the last administration of SACT. Age (ORs 0.412), ECOG-PS (ORs 11.533), primary cancer site of upper GI cancers (ORs 2.205), the number of comorbidities (ORs 0.207), MTAs (ORs 3.139), and ICIs (ORs 3.592) were significantly related factors within 30 days of death. The median survival time (MST) of patients with PS 3–4 was 29 days, while that of patients with both PS 0–2 was 76 days. The prevalence rate of delirium with MTAs was 17.5%, which was significantly lower than that of patients without it (31.8%). The prevalence rate of the mean dose of opioids in patients with ICIs was 97.9 mg/day, which was significantly higher than that of patients without it (44.9 mg/day). Conclusions: Age, ECOG-PS, primary cancer site, the number of comorbidities, MTAs, and ICIs use were significant associated with SACT near EOL. Information on these factors may aid clinical decision making in referral to palliative care institutes.